Development of a chitosan‐based adhesive. Application to wood bonding. Issue 6 (14th June 2012) - Patel, Anil K.; Michaud, Philippe; Petit, Emmanuel; de Baynast, Hélène; Grédiac, Michel; Mathias, Jean‐Denis
Abstract The potential of chitosan (CS) as wood adhesive was investigated in this study. The measurement of the bond strength of different CS‐based formulations was carried out using double‐lap shear tests. The best formulation tested was an adhesive composed of 6% of CS, 1% of glycerol, and 5 mmol/L of trisodium citrate dehydrate. Best bond strength from this formulation was found to be equal to 6.0 MPa in dried conditions and 1.6 MPa in wet conditions (specimens immersed for 3 h at 30°C in water). The failure in the double‐lap joint tests mainly occurred in wood. Finally, the penetration of the rhodamine‐labeled CS at 4% in the pinewood matrix was also studied using microtome and microscopy techniques to show interactions between CS‐based adhesive and wood. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2013